Classification of COVID-19 from Chest X-ray Images Using Transfer Learning - Mohammed, Lamyaa Alser; Elbashir, Murtada Khalafallah; Babikir, Gais Alhadi (Gezira Journal of Engineering and Applied Sciences; Vol 17 No 1 (2022), 2026)
Covid-19 descended from a virus strain called the corona, or coronavirus, in December 2019. It originated in Wuhan city of China, spread across the world, and became a pandemic. It should be noted that to prevent the further spread of this epidemic and to treat those infected with it quickly, researchers have been trying to develop effective methods to classify COVID2-19. One of these methods is the analysis of chest X-ray (CXR) images by radiologists, but this diagnosis has many drawbacks: it can take a long time, those radiologists are not available all the times, especially in remote areas, and the new features of COVID-19 are unknown to some radiologists. Therefore, it is necessary to implement an automatic classification system that helps doctors to classify COVID-19 in the early stages and provides a quick alternative diagnosis option to prevent the pandemic from spreading among people. This paper aimed to analyze and classify COVID-19-infected patients as infected (+ve) or not (−ve) from CXR images.  It should be noted that the images used in this paper were collected from two sources as follows:  440 positive COVID-19 CXR images were collected from the GitHub repository, and 440 normal CXR images were obtained from the Kaggle repository. Then, data preprocessing techniques were applied, specifically resizing and normalization, to suit the classification process. Subsequently, three different transfer learning models (Xception, InceptionV3, and MobileNetV2) were proposed for the classification of coronavirus pneumonia-infected patients using chest CXR radiographs. Moreover, the experimental results obtained from the pre-trained Xception model have provided the highest classification performance with 99.43% accuracy, 99% precision, 99% recall, and 99% F1-score. It should be noted that, to the best of our knowledge, the best state-of-the-art model achieves an accuracy of 97%, precision of 99%, recall of 94 %, and F1-score of 91%. So, the results of the proposed model (Xception) are the best achieved so far. Therefore, the pre-trained Xception model could contribute great importance to the automatic classification of COVID-19 from CXR images.